Understanding Needs Embodiment: A Theory-Guided Reanalysis of the Role of Metaphors and Analogies in Understanding Science - Niebert, K.; Marsch, S.; Treagust, David (John Wiley and Sons Inc., 2012)
Many authors stress the importance of basing teaching on students' prior knowledge. To build a bridge between students' everyday knowledge and scientific concepts, the role of metaphors and analogies came into the focus of the science education community during the past two decades. Approaches using metaphor-based teaching strategies often regard metaphors and analogies as teaching tools that can be adopted by a teacher. On the basis of the theoretical framework of experientialism, we argue that not only teaching but also thinking about and understanding science without metaphors and analogies is not possible. An analysis of studies dealing with metaphors and analogies in science education shows that instructional analogies and metaphors are often not understood as intended or not used by students in their own explanations. By reanalyzing 199 instructional metaphors and analogies on the basis of a metaphor analysis, we show that it takes more than making a connection to everyday life to communicate science fruitfully. We show that good instructional metaphors and analogies need embodied sources. These embodied sources are everyday experiences conceptualized in, for example, schemata such as containers, paths, balances, and up and down. For the analysis, we introduce the concept of conceptual metaphors for analyzing metaphors as well as analogies.